Numerical study on the supersonic gas-solid two-phase injection mechanism of needle-free syringe - Xiao Mo; Yang Xiao; Kai-Xiong Qing; Feng Zhang; Hongshi Yu (PLoS ONE, 2025)
Supersonic gas-solid injection technology finds extensive use in drug particle delivery systems. However, the combined impact of particle diameter and mass flow rate on the delivery efficiency remain insufficiently explored. Within the Euler-Lagrange framework, this study utilizes the discrete phase method (DPM) for the numerical simulation of supersonic gas-particle flow in a needle-free injector. After validating the model’s accuracy with experiment results, further investigations were conducted into the influences of particle size and mass flow rate on particle behavior and flow field properties. The results indicate that the impact of larger particles on the compressible structure is stronger, while higher mass flow rate absorbs greater energy from the gas phase, reducing the gas expansion capacity, which results in lower velocity, Mach number, and higher temperature. The jet core zone is approximately x/X = 0.3 in length. Outside core zone, the gas velocity rapidly decays and temperature rises sharply. Within the jet core zone, drug particles are accelerated and cooled, while beyond core zone, they decelerate and heat up. The strongest inter-phase interactions occur primarily in the nozzle expansion area and the jet core zone. Smaller particles reach maximum velocity upstream. This implies that in designing needle-free injectors, the nozzle-to-skin distance must match the drug particle diameter to achieve maximum penetration effectiveness. Furthermore, the particle temperature decreases with smaller sizes. As the particle diameter rises from 10 μm to 100 μm, the minimum temperatures of the particles are 145 K and 264 K, respectively, indicating the need to match the particle diameter with the minimum temperature at which the drug particles remain effective. Additionally, higher mass flow rate doses reduce injection velocity and penetration ability, necessitating the rational control of the administered dose range. These results offer significant theoretical guidance for the design and improvement of needle-free injection.